The comparative advantage of the U.S. shadow banking system and the role of the U.S. dollar. Issue 1 (3rd April 2019) - Tokunaga, Junji
Abstract: What facilitated European banks to expand their balance sheets denominated in the US dollar across the Atlantic through U.S. shadow banking system in the 2000s, despite the creation of the euro in 1999? In order to the question, this article argues that the European banks' balance sheets denominated in the dollar depended on the comparative advantage of the U.S. shadow banking system over one in the Eurozone in term of financial market side institutional side, resulting in the U.S. dollar reign in the shadow banking system in the 2000s. In conclusion, as far as the dominant position of the dollar in the shadow banking system, the U.S. dollar standard system has been as asymmetric as ever in the 2000s, rather than less asymmetric.